Cultural Communication Messages in the Dabus Traditions of Ternate and Tidore - Makbul A. H Din; Mubaddilah Rafa'al; Asri Ode Samura; Muhdi Alhadar (Yayasan Darussalam Bengkulu, 2026)
The formation of cultural communication messages, the meanings and symbols ingrained in the Dabus culture, the rituals used to transmit cultural messages, and the parallels and discrepancies between Ternate and Tidore are all examined in this study. The study investigates the subjective experiences of Dabus performers and participants using a qualitative phenomenological approach, emphasizing processes, motives, and messages. Purposive sampling was used to choose informants based on their involvement, competence, and experience. Observation, in-depth interviews, and document analysis were used to gather data, which was then inductively evaluated to find new meaning patterns. The results demonstrate how ritual symbols, social contact, and group involvement are used in the Dabus tradition to generate cultural communication messages that reflect religious, social, and historical significance. Through ceremonial phases and group activities, the tradition serves as a vehicle for the symbolic communication of religious ideals, bravery, social unity, and collective identity. While the ritual's role as a symbolic medium for communicating religious beliefs and social unity is comparable in all locations, the focus on meaning and symbolic orientation is different.